ARTISTIC CREATIVITY AS A PHENOMENON OF CULTURE AND SPIRITUALITY (AXIOLOGICAL APPROACH) - Allayarova Marhabo Mavlyanovna (Web of Journals Publishing, 2023)
This article focuses on the analysis of the issue of raising the spiritual world of our children, educating them in the spirit of national and universal values, and forming talents and abilities. In this process, it is important to study and analyze the issue of individual artistic creativity, which is one of the important factors in forming the spiritual education of young people. It is highlighted that artistic creativity serves as an important factor in the process of spiritual growth, the development of a person with a philosophical worldview, and the process of self-realization in our society. It has been studied that the essence of artistic creation is the phenomenon of spirituality and culture in the improvement of the person who is its owner.
Keywords: Spiritual-ideological threats, perfect person, artistic creativity, works of art, social ideal, aesthetic ideas, artistry, aesthetic education, objective conditions, subjective factors.